Axial-Symmetric Diffraction Radiation Antenna with a Very Narrow Funnel-Shaped Directional Diagram - Yuriy Sirenko; Seil Sautbekov; Merey Sautbekova; Nataliya Yashina; Nursaule Burambayeva; Assel Begimova (Applied Sciences, 2021)
The paper is focused on reliable modeling and analysis of axially symmetric radiators with a very narrow (throat) funnel-shaped radiation pattern. When such a diagram is formed, a wave analogue of Smith–Purcell coherent radiation is realized—the surface wave of a radial dielectric waveguide ‘sweeps out’ with its exponentially decaying part a concentric periodic grating, the fundamental spatial harmonic of which, propagating without attenuation in a direction close to the symmetry axis of the structure, generates a radiation field with the required characteristics.